2011
DOI: 10.3945/jn.111.139121
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum Vitamin D Is Associated with High Risk of Diabetes in Korean Adults,

Abstract: Vitamin D may play a role in glucose metabolism. A low vitamin D level has been associated with increased risk of diabetes mellitus, but the association has not been confirmed in Asians. Our objective was to examine the association of serum 25-hydroxyvitamin D [25(OH)D] levels with insulin resistance and diabetes mellitus in Korean adults based on a large population-based survey. Cross-sectional analyses were carried out on 5787 Korean adults (2453 men and 3334 women) who were 20 y or older and participated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
68
2
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 23 publications
6
68
2
4
Order By: Relevance
“…Recently, Gagnon et al (4) prospectively demonstrated that lower 25(OH)D levels are associated with increased HOMA-IR and risk of metabolic syndrome in Australian adults. In cross-sectional studies of Chinese (5) and Korean adults (6) , VitD status was inversely related to HOMA-IR. Low 25(OH)D levels are also significantly related to an increased risk of metabolic syndrome in Chinese adults (5) and T2DM in Korean adults (6) .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, Gagnon et al (4) prospectively demonstrated that lower 25(OH)D levels are associated with increased HOMA-IR and risk of metabolic syndrome in Australian adults. In cross-sectional studies of Chinese (5) and Korean adults (6) , VitD status was inversely related to HOMA-IR. Low 25(OH)D levels are also significantly related to an increased risk of metabolic syndrome in Chinese adults (5) and T2DM in Korean adults (6) .…”
Section: Discussionmentioning
confidence: 99%
“…In cross-sectional studies of Chinese (5) and Korean adults (6) , VitD status was inversely related to HOMA-IR. Low 25(OH)D levels are also significantly related to an increased risk of metabolic syndrome in Chinese adults (5) and T2DM in Korean adults (6) . Consistent with studies of adult populations (4)(5)(6)8) , cross-sectional nationwide studies of paediatric populations have consistently reported an inverse association between 25(OH)D levels and fasting hyperglycaemia and/or increased HOMA-IR, after adjustment for BMI (9,10) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations